(untitled) (Nepalese Journal of Development and Rural Studies, 2020)
Gender equations in any society are more or less anchored to cultural legacies. Nepali cosmologies constructed based on Hindu religious tradition, manifests the provision of Vedic societies in its present-day social structure, especially in gender. In the ancient times, women enjoyed equal rights and privileges as men, but with the rise of nation states, incidents of wars and conflicts multiplied for territorial expanse and security. This put male on the preference as martial and warring gender, and women started being confined to domestic responsibilities. This slowly crept into the social structure, and women have been suffering since then for lack of basic rights. The status is, however, changing because of recent political developments, that not only educated women vis-à-vis their rights, but also empowered them for various economic and social activities that contributed to their self-reliance. This article critically analyses changing value systems in the Nepalese society and the corresponding social and political transformation that has greatly altered the status of women. Much is yet to be done to bring the two genders in an equitable footing, but the gradual changes are a welcome sign towards gender equality and self-reliance.